Family Social Support for Refugees of Flash Flooding Disaster on The Temporary House in Rusunawa Gandasari (Shelter) of Garut Regency of Indonesia 2017 - Hidayat, Dian Roslan; Fatihudin, Mochamad (Science Techno Health Journal, 2023)
A flash flood is a flood that appears suddenly due to continuous rain, sliding rapidly from the high ground to the lower surface. Natural disasters challenge the affected areas, the environment, and communities to rise up and take control of their lives and future. The success of this effort is directly related to the capacity of victims to rebuild their social structures and organizations. Efforts to bounce back will require social support from families, communities and victims themselves. The general objective of this research is to know the family social support to refugees of Victims flash flooing disaster at The Temporary House of Rusunawa Gandasari District of Garut. The research method used is quantitative descriptive, with sample 66 refugees, the data retrieval technique is done by using questionnaire. Result of research and conclusion of some respondents stated that flash floods flood victims in Rusunawa Gandasari Garut regency did not get emotional support, some of did not get support from family appreciation, most of respondents stated that refugees flash floods victims in Rusunawa Gandasari Garut regency got support instrument Of the family and Most of the respondents stated that the refugees flash floods victims in Rusunawa Gandasari Garut regency did not get support from family information. It is recommended that the local government and family provide support to safety the victim flash floods during the evacuation.